Design and development of a multi-player iPad game portal application - Wu, Di. (2011)
With enormous popularity of Apple products (iPad, iPhone and iPod touch) world-wide, iOS applications have demonstrated great favours among Apple product users. This project provides a full design and development process for a multi-player iPad game portal application (Chinese chess) using web application development language (HTML, CSS, PHP, JavaScript and MySQL) and Objective-C.